Effects of Including Sprints in One Weekly Low-Intensity Training Session During the Transition Period of Elite Cyclists - Almquist, Nicki Winfield; Løvlien, Ine; Byrkjedal, Per Thomas; Spencer, Matt; Kristoffersen, Morten; Skovereng, Knut; Sandbakk, Øyvind; Rønnestad, Bent R. (Frontiers in Physiology, 2020)
The purpose of this study was to investigate the effects of including 30-s sprints in one weekly low-intensity training (LIT) session during a 3-wk transition period in elite cyclists. Sixteen male elite cyclists (maximal oxygen uptake, VO2max: 72±5 mL·kg-1·min-1) reduced their training load by 60% for 3 wks from the end of competitive season and performed only LIT (CON) or included 30-s sprints in one weekly LIT-session (SPR). Performance and physiological capacities were evaluated during a prolonged ( 2.5 hrs) test-session, including a strength test, a submaximal blood lactate profile test, an incremental test to exhaustion to determine VO2max, 1 h continuous cycling including 4 maximal 30-s sprints, and a 20-min all-out test. In addition, mental recovery was evaluated using the Athlete Burnout Questionnaire. The only significant between-group change during the transition period was an 8±11% larger improvement in 30-s sprint performance in SPR compared to CON (SPR: 4±5%, CON: -4±5%, p= .01). Although not different from CON, SPR maintained 20-min all-out performance (-1±5%, p= .37) and fractional utilization of VO2max (1.9±6.1 %-points, p= .18) during the 20-min all-out test, whereas corresponding declines were observed in CON (-3±5%, p= .04, and -2.5±2.9 %-points, p= .02, respectively). Power output at 4 mmol·L-1 blood lactate concentration decreased similarly in SPR (-4±4%, p= .02) and CON (-5±5%, p= .01), while VO2max, maximal aerobic power (Wmax), and total burnout score were unaffected in both groups. Including sprints in one weekly LIT-session in the transition period improves sprint performance and maintains 20-min all-out power and fractional utilization of VO2max without compromising mental recovery. Inclusion of sprints in LIT-sessions may therefore be a plausible, time-efficient strategy during short periods of reduced training.